Otolaryngology Providers Must Be Alert for Patients with Mild and Asymptomatic COVID-19. (June 2020) - Cheng, Xiaoting; Liu, Jialin; Li, Ning; Nisenbaum, Eric; Sun, Qing; Chen, Bing; Casiano, Roy; Weed, Donald; Telischi, Fred; Denneny, James C.; Liu, Xuezhong; Shu, Yilai
More than half of COVID-19 patients are afebrile early in the disease course, yet mildly ill or asymptomatic patients can still spread SARS-CoV-2 with high efficiency. Atypically presenting patients may be seen in noninfectious disease settings such as otolaryngology, which is a specialty prone to occupational exposure. Otolaryngologists have been infected with COVID-19 at higher rates than other specialties in China and other countries. Otolaryngology providers should maintain high clinical suspicion for mild and asymptomatic COVID-19 patients. Protective strategies should be implemented including preappointment screening, triaging, restriction of nonurgent visits and surgeries, telemedicine, and appropriate personal protective equipment use.